INCREASING STUDENT LEARNING OUTCOMES THROUGH THE IMPLEMENTATION OF REASONING AND PROBLEM SOLVING (RPS) MODELS ON STRUGGLING MATERIALS FACING THE THREAT OF DISINTEGRATION IN THE CLASSROOM XII MIPA 1 SMA NEGERI 1 MOJOSARI - Koestiono Koestiono (Sean Institute, 2022)
Initial observation results at SMA Negeri 1 Mojosari the daily test scores for class XII MIPA 1 were obtained . More than 50% are not complete in learning . The number of students who have not completed is 1 2 students with a percentage of 60% completeness. Based on this description, it shows that the results of learning the material for the struggle to face the threat of disintegration do not reach the minimum completeness criteria. Low learning outcomes due to the application of inappropriate learning models, passive students in learning, no assessment of assignments. The purpose of this study was to analyze the increase in learning outcomes for class X I I MIPA 1 SMA Negeri 1 Mojosari , through the application of the Reasoning And Problem Solving (RPS) learning model . To improve student learning outcomes on the subject of the struggle against the threat of disintegration , a classroom action research was conducted which consisted of two cycles. Each cycle consists of the stages of planning, implementing, observing and reflecting. The subjects of this study were students of SMA Negeri 1 Mojosari Class X I I MIPA 1 academic year 2017/2018. The data collection instrument in this study was an evaluation question for the cognitive domain which was carried out at the end of each cycle. Based on the results and discussion it can be concluded that learning using the Reasoning And Problem Solving (RPS ) learning model makes it easy for teachers to learn, makes learning centered on students, completes learning outcomes, and can teach and train student character behavior. The implementation of lesson plans was in good category with an average score of 3.0 in the first cycle and 3.27 in the second cycle. Student activity reached 85.26% in the first cycle and rose to 92.22%. In the aspect of scientific behavior both cycles are in the good category. Completeness of learning outcomes also shows an increase, from 75% in the first cycle to 92.86% in the second cycle.